Austrian Business Cycle Theory: Did Iceland go through an Austrian Business Cycle? - Ragnar Haukur Ragnarsson 1978- (2012)
The question this research tries to answer is if an artificial credit expansion caused the Icelandic economy to go into an Austrian style business cycle in the first decade of this century. To answer that question data from the Statistic of Iceland and the Central Bank of Iceland will be studied. The period that will be looked at is the years from 2001 until 2010. The framework that is used is taken from Jesús Huerta de Soto´s book “Money, Bank Credit, and Economic Cycles”, in that book de Soto lays out a framework that can be used to find empirical evidence of an Austrian business cycle. The boom and bust cycle is broken up into different stages; scenarios which the economy would go through under each stage are listed. In this research economic data are shown graphically under each stage to try to see if the economy went through the different scenarios the Austrian Business Cycle Theory predicts it would go through under an artificial credit expansion.